The effect of vitamin D and magnesium supplementation on the mental health status of attention-deficit hyperactive children: a randomized controlled trial - Mostafa Hemamy; Naseh Pahlavani; Alireza Amanollahi; Sheikh Mohammed Shriful Islam; Jenna McVicar; Gholamreza Askari; Mahsa Malekahmadi (BMC, 2021)
Abstract Background Attention-Deficit / Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder, characterized by varying severity in attention deficit and hyperactivity. Studies have shown deficiencies in the serum level of magnesium and vitamin D in people with ADHD. The aim of this study is to determine the effect of vitamin D and magnesium supplementation on mental health in children with ADHD. Methods We conducted a randomized, double blind, placebo-controlled clinical trial of 66 children with ADHD. Participants were randomly allocated to receive both vitamin D (50,000 IU/week) plus magnesium (6 mg/kg/day) supplements (n = 33) or placebos (n = 33) for 8-weeks. Strengths and difficulties questionnaire was used to evaluate children's mental health at baseline and the end of the study. Results After eight weeks of intervention, the serum levels of 25-hydroxy-vitamin D3 and magnesium increased significantly in the intervention group compared with the control group. Also, children receiving vitamin D plus magnesium showed a significant reduction in emotional problems (p = 0.001), conduct problems (p = 0.002), peer problems (p = 0.001), prosocial score (p = 0.007), total difficulties (p = 0.001), externalizing score (p = 0.001), and internalizing score (p = 0.001) compared with children treated with the placebo. Conclusion Vitamin D (50,000 IU/week) and magnesium (6 mg/kg/day) co-supplementation for a duration of 8-weeks could improve the behavioral function and mental health of children with ADHD. However, further well-designed studies with a larger sample size are needed. Trial registration IRCT2016030326886N1 .